2012
DOI: 10.1530/eje-12-0660
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokeratin 19 fragments: a dedifferentiation marker in advanced thyroid cancer

Abstract: Background: This study was undertaken to evaluate serum cytokeratin 19 fragment (Cyfra 21.1) expressions in patients with advanced thyroid carcinoma and to explore the relationship between serum Cyfra 21.1 and the degree of radioiodine ( 131 I) avidity of thyroid carcinoma cells. Methods: Enrolled were 76 consecutive patients with advanced thyroid carcinoma submitted to high-activity 131 I treatment. In each patient, serum thyroglobulin (Tg) and Cyfra 21.1 were measured before 131 I administration and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Furthermore, this smallest known acidic cytokeratin is not paired with a basic cytokeratin in epithelial cells. It is specifically expressed in the periderm, the transiently superficial layer that envelops the developing epidermis [15]. CK19 is expressed in simple epithelium and the basal cells of squamous epithelium and is mainly interpreted as a marker of dysfunctional epithelial differentiation [8], however the underlying biology is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this smallest known acidic cytokeratin is not paired with a basic cytokeratin in epithelial cells. It is specifically expressed in the periderm, the transiently superficial layer that envelops the developing epidermis [15]. CK19 is expressed in simple epithelium and the basal cells of squamous epithelium and is mainly interpreted as a marker of dysfunctional epithelial differentiation [8], however the underlying biology is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plasma-based assays of pHER2-derived phosphopeptides may hold a promising predictive and diagnostic value. Similarly, fragments of cytokeratins (CKs) in serum are already being used for the prediction of prognosis of various cancers (39, 62, 63). We have identified several phosphorylation sites on CK8, CK18, and CK19 as luminal specific and like pHER2, also tissue and tumor-specific phosphopeptides carrying distinct patterns could be used to increase specificity of serum CK assays.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent study showed that loss of canal of Hering marked with K19 staining appeared in the early stage of primary biliary cirrhosis (PBC), and this finding may provide support to clinical diagnosis of PBC [51]. Further, K19 is also often expressed in a variety of human cancers, such as urothelial bladder carcinoma, advanced thyroid cancer and hepatocellular carcinoma (HCC) [10,[44][45]52]. Specifically, in the subtype of HCC which characterized with expression of K19, it is histologically poorly differentiated and exhibit aggressive tumour activity.…”
Section: Function Of Keratinsmentioning
confidence: 96%
“…the lining of gastroenteropancreatic and hepatobiliary tracts) are among tissues with the highest K19 expression (Table 2) [10,[44][45]. Of note, K19 expression is restricted to the biliary system in adult liver under physiological condition, and therefore, K19 represents as an established marker for cholangiocytes [46].…”
Section: Function Of Keratinsmentioning
confidence: 99%
See 1 more Smart Citation